Benefits from living together? Clades whose species use similar habitats may persist as a result of eco‐evolutionary feedbacks. Issue 1 (23rd November 2016) - Prinzing, Andreas; Ozinga, Wim A.; Brändle, Martin; Courty, Pierre‐Emmanuel; Hennion, Françoise; Labandeira, Conrad; Parisod, Christian; Pihain, Mickael; Bartish, Igor V.
Summary: Recent decades have seen declines of entire plant clades while other clades persist despite changing environments. We suggest that one reason why some clades persist is that species within these clades use similar habitats, because such similarity may increase the degree of co‐occurrence of species within clades. Traditionally, co‐occurrence among clade members has been suggested to be disadvantageous because of increased competition and enemy pressure. Here, we hypothesize that increased co‐occurrence among clade members promotes mutualist exchange, niche expansion or hybridization, thereby helping species avoid population decline from environmental change. We review the literature and analyse published data for hundreds of plant clades (genera) within a well‐studied region and find major differences in the degree to which species within clades occupy similar habitats. We tentatively show that, in clades for which species occupy similar habitats, species tend to exhibit increased co‐occurrence, mutualism, niche expansion, and hybridization – and rarely decline. Consistently, throughout the geological past, clades whose species occupied similar habitats often persisted through long time‐spans. Overall, for many plant species, the occupation of similar habitats among fellow clade members apparently reduced their vulnerability to environmental change. Future research should identify when and how this previously unrecognized eco‐evolutionary feedback operates. Contents Summary 66 I. Entire clades decline while others persist; we suggest this might reflect an eco‐evolutionary feedback between habitat similarity among clade members, their co‐occurrence, and their reduced vulnerability to environmental change 67 II. Definitions, and methods used to infer tentative evidence from published results 68 III. The interface between variation in habitat use within clades and the assembly of local communities: clade members occupying similar habitats tend to locally co‐occur 69 IV. The mainstream hypotheses in community ecology imply that co‐occurrence with fellow clade members is detrimental, but the evidence is equivocal 70 V. We suggest that co‐occurrence with fellow clade members is often beneficial and we present evidence 73 VI. There is tentative evidence for an eco‐evolutionary feedback between habitat similarity among clade members, their co‐occurrence, and their reduced vulnerability to environmental change 75 VII. Conclusions and future directions 77 Acknowledgements 78 References 78